2017
DOI: 10.1016/j.omtn.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Targeted Plasmonic Photothermal Therapy of Cancer

Abstract: Novel nanoscale bioconjugates combining unique plasmonic photothermal properties of gold nanoparticles (AuNPs) with targeted delivery using cell-specific DNA aptamers have a tremendous potential for medical diagnostics and therapy of many cell-based diseases. In this study, we demonstrate the high anti-cancer activity of aptamer-conjugated, 37-nm spherical gold nanoparticles toward Ehrlich carcinoma in tumor-bearing mice after photothermal treatment. The synthetic anti-tumor aptamers bring the nanoparticles pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The practicality of AuNP-based PTT has been demonstrated through in vitro and in vivo studies [ 158 , 162 , 163 ]. When the AuNPs are exposed to light, they can convert the absorbed light energy into thermal energy within picoseconds [ 57 , 158 , 159 ], consequently activating cell death via necrosis or apoptosis in the target cells or tissues.…”
Section: Biological Application Of Aunpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practicality of AuNP-based PTT has been demonstrated through in vitro and in vivo studies [ 158 , 162 , 163 ]. When the AuNPs are exposed to light, they can convert the absorbed light energy into thermal energy within picoseconds [ 57 , 158 , 159 ], consequently activating cell death via necrosis or apoptosis in the target cells or tissues.…”
Section: Biological Application Of Aunpsmentioning
confidence: 99%
“…While the ones that absorb and emit light in the visible spectrum (AuNSs and hollow AuNPs) have been demonstrated to treat diseases that affect shallow tissues (up to a depth of 1 mm), which could be of benefit to superficial tumors [ 158 , 161 , 162 ], ocular surgery [ 164 , 165 ], focal therapy and vocal cord surgery [ 158 , 165 ]. Although the PTT effects of AuNSs are limited in vivo or for use in deep tissues, combination therapy or active targeting can be incorporated to facilitate target-specific effects [ 158 , 161 , 163 ]. The AuNPs in the combination therapy will serve dual functions as both drug sensitizer and a PT agent, and was shown to enhance anticancer effects of chemotherapeutic drugs [ 158 , 162 , 163 ].…”
Section: Biological Application Of Aunpsmentioning
confidence: 99%
“…For example, Topete et al demonstrated a nanotheranostic platform comprising poly(lactic‐ co ‐glycolic acid)/doxorubicin‐core@Au‐branched shell nanostructures, whereas Chen et al reported the coencapsulation of iron oxide nanoparticles and gold nanorods inside mesoporous silica beads, which displayed multimodal imaging ability, combined with improvements in stroke therapy . More recently, Kolovskaya et al proposed high anticancer activity of aptamer‐conjugated, spherical gold nanoparticles in tumor‐bearing mice upon photothermal treatment . Despite these efforts, several challenges are still to be overcome before nanoplasmonics can be implemented as a tool for in vivo biosensing and bioimaging.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the second structure of anti-EGFR aptamer attached on the surface of liposomes is fold correctly and enable cell internalization via the EGFR-mediated pathway. However, the second way is not suitable for these aptamers, such as TLS11a, [71] SRZ1, [101] AptS1, [102] and As42 or S13, [103] of which targeted receptor proteins on the positiveselection cells are not clear. Accordingly, SNPs conjugated with these aptamers just enable the delivery of drugs to specialized targeted cancer cells.…”
Section: Targeted Drug Deliverymentioning
confidence: 99%